2022
DOI: 10.1101/2022.12.16.520702
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ClpP/ClpX deficiency impairs mitochondrial functions and mTORC1 signaling during spermatogenesis and meiosis

Abstract: Caseinolytic protease proteolytic subunit (ClpP) and caseinolytic protease X (ClpX) are mitochondrial matrix peptidases that activate mitochondrial unfolded protein response (mtUPR) to maintain protein homeostasis in the mitochondria. However, the role of ClpP and ClpX in spermatogenesis remains largely unknown. In this study, we demonstrated the importance of ClpP/ClpX for meiosis and spermatogenesis with two conditional knockout (cKO) mouse models. We found that ClpP/ClpX deficiency reduced mitochondrial fun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Studies on the UPR mt and aging have demonstrated that Caseinolytic peptidase P (ClpP) deficiency induced activation of the mTOR pathway, thereby accelerating depletion of ovarian follicular reserves or impairing spermatogenesis. 12,48 Moreover, numerous studies have demonstrated the inhibitory effect of the mTOR pathway on chondrocyte autophagy during OA progression. 13−15 ClpP is a mitochondrial protease that is capable of degrading invalid proteins.…”
Section: Enhancing the Uprmentioning
confidence: 99%
“…Studies on the UPR mt and aging have demonstrated that Caseinolytic peptidase P (ClpP) deficiency induced activation of the mTOR pathway, thereby accelerating depletion of ovarian follicular reserves or impairing spermatogenesis. 12,48 Moreover, numerous studies have demonstrated the inhibitory effect of the mTOR pathway on chondrocyte autophagy during OA progression. 13−15 ClpP is a mitochondrial protease that is capable of degrading invalid proteins.…”
Section: Enhancing the Uprmentioning
confidence: 99%